Favorite Pets Learn to draw furry friends and cute companions step by step! - Legendre, Philippe (CA, USA Quartoknows publishing group, 2014)
Now even the youngest artists-in-training can learn to draw step by step with the exciting I Can Draw series. With these approachable, engaging instructions, children ages four years and older will discover how easy it is to draw a range of favorite animals and subjects. Animals Around the World teaches young artists how to draw a range of animals, such as a koala, camel, lion, panda, giraffe, tiger, rhinoceros, and more, from exotic destinations all around the world. Animals Around the World opens by introducing young artists to a small selection of essential drawing tools and materials before moving on to a variety of easy-to-follow step-by-step drawing lessons. Packaged in a softcover binding with 64 pages of colorful artwork, each drawing lesson is specially formatted for a young audience. Animals Around the World teaches inspiring artists how to draw almost any animal by starting with a basic shape, such as an oval, a circle, or a triangle, and following along as each step-by-step instruction guides the artist to a completed color masterpiece. With the I Can Draw series, and Animals Around the World, children will love drawing their way through hours of artistic adventure
Drawing
"64 pages of drwaing fun! contains fun facts, quizzes, color photos, amd mich more!"
2
Keywords: Drawing; Juvnile nonficion